2012
DOI: 10.1167/iovs.11-8449
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Is Associated with Altered Gene Expression in AMD

Abstract: Comparison of DNA methylation, together with mRNA levels, revealed significant differences between AMD versus normal retinas. The evidence presented suggests that GSTM1 and GSTM5 undergo epigenetic repression in AMD RPE/choroid, which may increase susceptibility to oxidative stress in AMD retinas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 67 publications
2
93
0
Order By: Relevance
“…Likewise, relatively small methylation differences have be linked to changes in gene expression, which hint at potential functional effects of our observed methylation differences. 16 This is one of the first studies to show a relationship between DNAm and AMD, [38][39][40] but many questions remain. Did the disease-associated differential methylation observed in the blood and retina arise prior to the onset of AMD and contribute to the disease phenotype or was it a secondary effect of the disease process or treatment?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, relatively small methylation differences have be linked to changes in gene expression, which hint at potential functional effects of our observed methylation differences. 16 This is one of the first studies to show a relationship between DNAm and AMD, [38][39][40] but many questions remain. Did the disease-associated differential methylation observed in the blood and retina arise prior to the onset of AMD and contribute to the disease phenotype or was it a secondary effect of the disease process or treatment?…”
Section: Discussionmentioning
confidence: 99%
“…meQTL analysis in Illumina 450K samples Observed high-quality genotypes on 290 subjects with Illumina 450k data (out of 298, 97.3%) were obtained from dbGaP (accession: phs000182.v2.p1). SNPs on chromosome 10 were phased using ShapeIT, 37 and the 6 megabase area flanking the AMD risk SNP (chr10:121214448-127214448) was imputed up to the latest 1000 Genomes Phase 3 reference panel using Impute2 38 to obtain genotype calls for rs10490924 and rs72631113. Using the previously calculated surrogate variables (SVs, see above), we performed meQTL analyses separately within AMD patients (NV and GA together) and controls, at both SNPs, using the linear model of the form: Meth j D a C bSNP j C zSV j C e j for person j.…”
Section: Gwas Enrichment Analysismentioning
confidence: 99%
“…(2012) [128] GSTP1 Glutathione S-transferase P Codes for an enzyme that has an important role to play in the prevention of oxidative damage. …”
Section: Computational Models Of the Dna Methylation Cyclementioning
confidence: 99%
“…Glutathione S-transferase PI (GSTP1) is a scavenger of reactive oxygen species (ROS) and its absence could reduce protection from genome-damaging oxidants, resulting in increased vulnerability to further oxidative insults. Hunter et al 28 found that mRNA levels of glutathione S-transferase isoforms mu1 (GSTM1) and mu5 (GSTM5) were significantly reduced in AMD patients vs age-matched controls in retinal pigment epithelium (RPE)/choroid and neurosensory retina. This corresponded to hypermethylation of the GSTM5 promoter.…”
Section: Dna Methylation Changes Affect Antioxidant Gene Expression Imentioning
confidence: 99%